The new views on the state of the gut microbiota in obesity and diabetes mellitus type 2 - Elena V. Pokrovskaya (Endocrinology Research Centre, 2019)
Obesity is a worldwide problem of the last century, the prevalence of which has reached pandemic proportions in developed countries. Over the past few years, a considerable amount of data has been gathered, reporting a direct link between changes in gut microbiota and the development of obesity, as well as related diseases, primarily, diabetes mellitus type 2. The elaboration of optimal methods of prevention and treatment regimens of these diseases needs to structure the existing knowledge about the mechanisms of development of metabolic disorders, the role of intestinal microbiota in the latter and possible therapeutic “targets”. This review examines the role of microorganisms in the human body, with the main focus on the developmental origins of metabolic disorders using animal models and accumulated experience of research on their effects on the human body, and also discusses possible treatment options, including bariatric surgery, fecal microbiota transplantation, the use of pre- and probiotics and certain particular groups of glucose-lowering drugs.